PENGARUH MEDIA PEMBELAJARAN POP UP BOOK DENGAN TEKNIK V-VOLDING UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA MATERI TUMBUHAN IPAS KELAS IV SEKOLAH DASAR - Rani Yulisna; Wahyu Kurniawati; Heru Purnomo (LPPM Universitas Cipta Mandiri, 2025)
The research on Pop Up Book learning media with the V-Volding technique is motivated by the low academic performance in the IPAS subject for 4th-grade elementary school and the lack of use of learning media. This research and development uses the Research and Development (R&D) method model, employing the 4D model. The study was conducted at SD N Ngrukeman, in the Kasihan District, Tamantirto Village, Yogyakarta. Data collection for this research was carried out through interviews, tests, and questionnaires. The results of this study provide validation from expert validators in media, IPAS experts, as well as responses from students and teachers, indicating that the pop up book learning media received a “very valid” criterion in the validation assessment from media and material experts. Meanwhile, the results of the normality test using Shapiro Wilk show that the data is normally distributed, as well as in the Sample T-test which obtained a significance level of 0.00<0.05, meaning that the use of the media. Meanwhile, the results of the normality test using Shapiro Wilk show that the data is normally distributed. Similarly, the Sample T-test obtained a significance of 0.00<0.05, meaning that the use of this learning media is capable of improving students' academic performance, as evidenced by the increase in average pretest and posttest scores of 57.5 using the Pop Up Book learning media on this plant topic.